Breaking the Silence: Exploring the Prevalence and Effects of Sexual Harassments in Sri Lanka's Workplaces (Vallis Aurea, 2023)
Purpose: Sexual harassment (SH) in the workplace is a serious issue affecting many Sri Lankan women. Despite ongoing efforts, SH remains widespread and continues to negatively impact women’s lives. This study aimed to explore how SH affects the personal lives of female employees.Design/Methodology: A quantitative approach was used, with 351 female employees selected through convenience sampling. Participants completed standardized questionnaires. Correlation and regression analyses were conducted to assess the impact of SH. Results revealed that SH is linked to various negative outcomes, including psychological issues such as depression, anxiety, and fear; physical symptoms like sleep disturbances, low energy, and chronic pain; and decreased job satisfaction, motivation, productivity, and strained workplace relationships.Findings: The findings highlight the urgent need for increased awareness and preventative action in workplaces. Organizations must implement comprehensive SH policies, provide training to staff and management, and establish clear reporting and response systems.Originality: This study sheds light on the serious consequences of SH on the personal lives of Sri Lankan women. It emphasizes the need for collective, proactive efforts from organizations to ensure a safe and inclusive work environment for all employees.